The Effect of Rosmarinic Acid on Oxidant-Antioxidant Balance in Acetaminophen-Induced Hepatotoxicity in Male Rats - Nahid Azarmehr; Parisa Afshar; Zeinab Khizab; Zahra Moslemi; Amir Hossein Doustimotlagh (Fasa University of Medical Sciences, 2020)
Background & Objective: High dose of acetaminophen (APAP) causes detrimental side effects such as hepatotoxicity. In the present study, the effects of Rosmarinic acid on oxidant-antioxidant balance in APAP-induced hepatotoxicity in male rats were investigated. Materials & Methods: A total of 18 male Wistar rats were divided into three groups: control (C), APAP (2 g / kg) and APAP + Rosmarinic acid (20 mg/kg). On the seventh day, after blood sampling, the rats were sacrificed and the number of biochemical parameters, oxidative stress markers and activity of antioxidant enzymes was measured. Statistical analysis was performed by SPSS software (V.17). Results: It was observed that the activity of alanine transaminase and aspartate transaminase enzymes significantly increased and the amount of protein carbonyl slightly increased in the APAP group compared to the control group. Glutathione peroxidase activity and total thiol levels were significantly reduced in the APAP group compared to the control group. Rosmarinic acid administration markedly reduced the activity of AST, ALT enzymes and amount of protein carbonyl compared to the APAP group while it significantly increased the activity of glutathione peroxidase and catalase enzymes. Conclusions: Rosmarinic acid reduces oxidative stress by preventing protein oxidation and increasing the activity of the antioxidant enzymes including glutathione peroxidase and catalase. The effect of hepatic protection of Rosmarinic acid may be due to its antioxidant properties and the trapping of free radicals by this compound.